2018
DOI: 10.1186/s12906-018-2228-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the potentially inappropriate Kampo medications to be used with caution among elderly patients taking any prescribed Kampo medications at a single centre in Japan: a retrospective cross-sectional study

Abstract: BackgroundFew studies have investigated the prevalence and characteristics of potentially inappropriate Kampo medication use among elderly ambulatory patients taking any prescribed Kampo medications.MethodsA retrospective cross-sectional study was conducted using electronic medical records. All patients aged 65 years or older who continued visiting internal medicine physicians and were prescribed any Kampo medications from January 2015 to March 2015 were included. The primary outcome was the proportion of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Therefore, this finding may be specific to Japan where herbal medications are often prescribed by physicians 16. Given that the potentially inappropriate use of traditional Japanese herbal medication among elderly patients may be common in Japan,17 our findings suggest that a strategy to improve the appropriateness of herbal medication use is needed. Moreover, given that accurate data on the safety of herbal medication use are lacking,18 monitoring the adverse events of herbal medications is also needed 19…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, this finding may be specific to Japan where herbal medications are often prescribed by physicians 16. Given that the potentially inappropriate use of traditional Japanese herbal medication among elderly patients may be common in Japan,17 our findings suggest that a strategy to improve the appropriateness of herbal medication use is needed. Moreover, given that accurate data on the safety of herbal medication use are lacking,18 monitoring the adverse events of herbal medications is also needed 19…”
Section: Discussionmentioning
confidence: 76%
“…Kampo is used by the elderly as a supplementary treatment to maintain mental and physical wellbeing [54]. A retrospective cross-sectional study in Japan reported that Glycyrrhizae radix , the most commonly used component of Kampo, was potentially associated with chronic kidney disease and uncontrolled hypertension in elderly patients [55]. This unconfirmed relationship is worthy of further exploration and evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, assuming that the proportion of patients who used CEHF Kampo medications was 6%, based on a previous study to determine the prevalence of potentially inappropriate use of Kampo medications among elderly patients in outpatient settings, 8 approximately 400 acute heart failure patients were needed to provide a precision of 3% for the calculation of the 95% confidence intervals (CIs) of the primary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the inappropriate use of prescribed Kampo medications might be common in Japan. 8 Certain components of Kampo medications can be harmful to cardiac function. [9][10][11][12][13][14][15][16] For example, licorice can cause heart failure through sodium retention.…”
Section: Introductionmentioning
confidence: 99%